Persecutive personality disorder among university students (Journal of the College of Basic Education, 2022)
There are many adjectives with which he described this era in which we live. It is the age of gods and the age of anxiety.The atom age, the computer age, and the last of these epithets, but not the least significant, is the age of turmoil.And that is because the contemporary man has begun to appear from the manifestations of thinking and behavior.The imbalance and turmoil in his life as much as it is an expression of the burden of contemporary life and the difficulty of copingwith its requirements (Kamal 1987), in addition to the social, educational and economic conditions.The hardships resulting from the situation to which the society in Iraq was subjected, including the segment of youth whoUniversity students constitute a large part of them, and although there are no accurate and clear statisticsabout these multiple problems, but some local studies indicated the prevalence of some manifestations ofPersonal disorders in Iraqi society.